Assessment of Alcohol-Based Hand Sanitizers for Long-Term Use, Formulated with Addition of Natural Ingredients in Comparison to WHO Formulation 1 - Francesca Fallica; Chiara Leonardi; Valeria Toscano; Debora Santonocito; Paola Leonardi; Carmelo Puglia (MDPI AG, 2021)
During the spread of COVID-19, many laboratories used the "Formulation 1" proposed by the World Health Organization to prepare hand sanitizers. Taking into consideration its ingredients and the prolonged use of hand sanitizers, "Formulation 1" (P1) was compared with two gel formulations (P2 and P3) prepared with the addition of natural emollients and two different viscosity enhancers to define their chemical-physical stability, biocidal efficacy, and in vivo acceptability and tolerability. P1 resulted in the most efficient biocide but was poorly tolerated by the skin and not acceptable in volunteer hedonic evaluation, especially in terms of irritation and drying effect, with an expectable reduction in the compliance. Moreover, its liquid formulation is unpractical and can cause ethanol evaporation. P2 and P3 proved to be both good products regarding pH and alcohol strength values. However, in terms of viscosity, texture, ease of use, and application, P3 seemed to be a better gel product than P2. Moreover, they were well tolerated by the skin, increasing the hydration of the stratum corneum, due to the addition of Calendula officinalis and Aloe vera. Despite a lower ethanol concentration than P1, P2 and P3 also showed a good biocide efficiency, with better results in P2. In conclusion, these gel formulations proved to be more convenient for long-term use with a good balance between efficacy, safety, and compatibility with the skin.